Revisión de la experiencia clínica en el manejo quirúrgico de la otoesclerosis - Délano R., Paul H.; Alvo V., Andrés; Panussis F., Felipe; Ojeda S., Alejandro; Stott C., Carlos (Revista Hospital Clínico Universidad de Chile, 2011)
Introduction: Otosclerosis is a disease that produces a conductive hearing loss. It consists of an abnormal bone growth called otospongiosis that develops a stapes fixation. It is a hereditary disease but the specific cause is unknown. Its surgical management has shown good audiometric results and low complication rates. Aim: To describe the clinical experience in our Unit, with bilateral and unilateral surgeries in patients with Otosclerosis. Methods: A retrospective study on clinical charts revision. Results: 415 patients underwent surgery for Otosclerosis. 359 patients had a unilateral procedure and 56 patients had a bilateral surgery (13,5%). Mostly women (67,9%). There was no difference between the results of both ears. The Average air-conductive hearing improvement in the first surgery was 29,9 ± 3,4 dB, and in the second surgery was 30,6 ± 3,4 dB. The most frequent complication was the section of thechorda tympani (2%). Discussion: The surgical treatment for Otosclerosis is a safe procedure with excellent audiometrical results and low complication rates. Our results are similar to those in literature. The number of this procedure has increased every year in our institution and we have demonstrated that surgery in both ears is safe with good results.